Risk factors for readmission in schizophrenia treated with combined psychoeducation and standard therapy. Issue 1 (26th January 2022) - Sugisawa, Satoru; Kurihara, Tatsuya; Nakano, Yukako; Tsuneoka, Toshiaki; Koya, Hiroaki; Nagai, Tsutomu; Ikeda, Tomohiro; Fujisawa, Naoko; Inamoto, Atsuko; Iwanami, Akira
Abstract: Background: We conducted a historical cohort study of patients with schizophrenia to identify more robust risk factors at discharge that contribute to readmission within a year. Methods and Findings: The subjects underwent brief psychoeducation during hospitalization. Multivariate analysis was conducted using factors selected in the univariate analysis. Using logistic regression analysis, the number of hospital admissions ( P  = .01) and Schedule for Assessment of Insight Japanese version score ( P  = .04) were identified as risk factors for readmission, with odds ratios of 0.70 and 1.18, respectively. Conclusions: These results suggest that improvement in insight and early intervention may lead to a more stable community life. Abstract : We conducted a historical cohort study of patients with schizophrenia to identify more robust risk factors at discharge that contribute to readmission within a year. The number of hospital admissions and Schedule for Assessment of Insight Japanese version score were identified as risk factors for readmission.